Исследование влияния механических характеристик материала на характер деформирования рабочих колес центробежных компрессоров - Бухолдин, Ю. С.; Левашов, В. А.; Львов, Геннадий Иванович; Костромицкая, Ольга Анатольевна (НТУ "ХПИ", 2006)
The influence of a yield stress value on character of elastoplastic deformation and elastic unloading of the working wheel under inertial loading is investigated. The realization of the large number of calculation variants by a of finite-element method shows, that there is a so-called critical value of a yield stress. It is not recommended to use materials having a yield stress lower of this critical value, for making of working wheels of centrifugal compressors, as it will result in redistribution of a deforming picture, appearance of the large bending moments and displacements, which after unloading do not disappear
Keywords: рабочее колесо; пластические деформации; посадка на вал; предел текучести